2019
DOI: 10.1016/j.mex.2019.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of performance of drought prediction in Indonesia based on TRMM and MERRA-2 using machine learning methods

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…A more recent study, Rahmati et al (2020) compared the performance of six different ML techniques [classification and regression trees (CART), boosted regression trees (BRT), random forests, multivariate adaptive regression splines (MARS), flexible discriminant analysis (FDA), and SVM] for mapping agricultural drought hazard in the southeast region of Queensland, Australia. Similar to Park et al (2016) and Kuswanto and Naufal (2019), they found that random forests had the best goodness-of-fit and predictive performance among the six models. Zaniolo et al (2018) contributed to the FRIDA (FRamework for Index-based Drought Analysis) for the automatic design of basin-customized drought indexes across different types of basins by applying a MLpowered variable selection algorithm.…”
Section: Advancement In the Use Of Machine Learning Techniques For Drought Predictionmentioning
confidence: 67%
See 2 more Smart Citations
“…A more recent study, Rahmati et al (2020) compared the performance of six different ML techniques [classification and regression trees (CART), boosted regression trees (BRT), random forests, multivariate adaptive regression splines (MARS), flexible discriminant analysis (FDA), and SVM] for mapping agricultural drought hazard in the southeast region of Queensland, Australia. Similar to Park et al (2016) and Kuswanto and Naufal (2019), they found that random forests had the best goodness-of-fit and predictive performance among the six models. Zaniolo et al (2018) contributed to the FRIDA (FRamework for Index-based Drought Analysis) for the automatic design of basin-customized drought indexes across different types of basins by applying a MLpowered variable selection algorithm.…”
Section: Advancement In the Use Of Machine Learning Techniques For Drought Predictionmentioning
confidence: 67%
“…Their findings suggest that among the three approaches, random forests provide the best performance for Standardized Precipitation Index (SPI) prediction. Similarly, Kuswanto and Naufal (2019) found the performance of random forests to be optimal when using SPI derived from Modern-Era Retrospective analysis for Research and Applications (MERRA-2) for drought prediction over the East Nusa Tenggara Province in Indonesia. A more recent study, Rahmati et al (2020) compared the performance of six different ML techniques [classification and regression trees (CART), boosted regression trees (BRT), random forests, multivariate adaptive regression splines (MARS), flexible discriminant analysis (FDA), and SVM] for mapping agricultural drought hazard in the southeast region of Queensland, Australia.…”
Section: Advancement In the Use Of Machine Learning Techniques For Drought Predictionmentioning
confidence: 96%
See 1 more Smart Citation
“…From the point of view of the households characteristics, further analysis using Random Forest method of Breiman (2001) can be used to investigate the importance factors influencing the decision to use the forecast. Random Forest has been proven to be a powerful machine learning method compared to others (Kuswanto and Naufal, 2019). The method confirmed that that the usage of the forecast is mainly influenced by the age of the household head.…”
Section: Resultsmentioning
confidence: 99%
“…Metode-metode yang secara umum digunakan untuk menangani kondisi seperti itu adalah metode dari pendekatan level data. seperti yang dilakukan oleh [3] yang menggunakan SMOTE sebagai metode untuk menangani ketidakseimbangan kelas pada dataset yang digunakan. Terdapat metode lain yaitu ADASYN yang merupakan pemutakhiran dari metode SMOTE.…”
Section: Pendahuluanunclassified